REVIEW ON AYURVEDA CONCEPTS ON THE REGIMEN OF FOOD AND DRINK CONSUMPTION - Nanayakkara Vidanagamage Yasangi Diloopa; Edirimuni Rodrigo Hathishiya Sujatha Silva Ediriweera (AYUSHDHARA, 2021)
This is a review conducted with the objectives of evolving the concepts of the regimens of the food consumption according to the Ayurveda. In comparison to the past decades, non communicable diseases are a burden to the present society. Non-healthy patterns and practices of the food consumption are proven as a major determinant factor to increase the non-communicable diseases. This has been proven by various studies. Hence, it is important to identify the healthy pattern and practices of food consumption. This review is based on the textual references in relation to Ayurveda medicine and journal articles. Ayurveda medicine which provided wide range of spectrum in food consumption, fulfilled with wholesome and non wholesome way of arrangement in the kitchen, qualities of the person who prepares the meals, methods of preparing meals, methods of offering the meal, way of selecting the meal, determining the quantity of food that is liable to be consumed, proper time for consuming food, things that should and should not be done before and after consuming meals, codes and ethics during the food consumption with conceptual justification based on the Ayurveda medicine. Some of these facts are proven by the modern science also. This knowledge can be utilized as a solution for the prevailing health burden in non-communicable diseases with a more advanced and scientific way.